Renal vasculitis in Colombia - F Ramírez; W Rojas; D Jaramillo; C Ochoa; CA Toro; Paul Méndez-Patarroyo; P Coral; J Cantillo; G Ramírez; G Quintana; JF Restrepo; F Rondón; et al. (Asociación Colombiana de Nefrología e Hipertensión Arterial, 2015)
A retrospective review of publications about primary vasculitis cases was performed from the Colombian medical literature, the clinical and pathological features are described. The Renal vasculitis occurred in 33.9% of cases of primary vasculitis reviewed and was more frequent in women. The main clinical, hematological, immunological variables and nephropathology and immunosuppressive treatments used findings are described.